A Highly Efficient Sandwich‐Like Symmetrical Dual‐Phase Oxygen‐Transporting Membrane Reactor for Hydrogen Production by Water Splitting. Issue 30 (31st May 2016) - Fang, Wei; Steinbach, Frank; Cao, Zhongwei; Zhu, Xuefeng; Feldhoff, Armin
Abstract: Water splitting coupled with partial oxidation of methane (POM) using an oxygen‐transporting membrane (OTM) would be a potentially ideal way to produce high‐purity hydrogen as well as syngas. Over the past decades, substantial efforts have been devoted to the development of supported membranes with appropriate configurations to achieve considerable performance improvements. Herein, we describe the design of a novel symmetrical membrane reactor with a sandwich‐like structure, whereby a largescale production (>10 mL min −1  cm −2 ) of hydrogen and syngas can be obtained simultaneously on opposite sides of the OTM. Furthermore, this special membrane reactor could regenerate the coke‐deactivated catalyst in situ by water steam in a single unit. These results represent an important first step in the development of membrane separation technologies for the integration of multiple chemical processes. Abstract : Sandwich‐like membrane reactor : H2 production by means of water splitting coupled with partial oxidation of methane (POM) is conducted in a sandwich‐like symmetrical dual‐phase membrane reactor. The infiltrated Ni nanoparticles (red spheres) significantly enhance the number of reactive sites and also catalyze the POM reaction. Furthermore, the membrane reactor can regenerate the coked catalyst in situ using steam.